HERITABILITY ESTIMATES OF SOME BODY MEASUREMENTS IN NILI RAVI BUFFALOES - H. Mirza; M. A. Khan; A. Waheed; M. Akhtar; S. M. Raihan- dilshad; Asim Faraz; H. M. Ishaq; Z. H. Kuthu (Journal of Animal and Plant Sciences, 2020)
Current study was conducted to find out heritability estimates of some body measurements of Nili Ravi buffaloes maintained at 5 Livestock Experiment Stations in Punjab Pakistan. Recording of body measurements was continued for 3 years since 2010 to 2012. Heritabilities of traits were estimated using BLUP (Best Linear Unbiased Prediction) evaluation techniques. Influencing factors such as age of the buffalo at scoring, stage of lactation, parity, herd and season were included in the model. Individual Animal Model was fitted under Restricted Maximum Likelihood (REML) Procedure. Data were analysed using the mixed model procedure of the Statistical Analysis Systems. Fixed effects observed to be significant in the initial analysis were included in the model for estimation of variance components from which genetic parameters were estimated. The ASREML set of computer programs was used to estimate heritabilities. Least squares means for head length, poll width, horn diameter, ear length, ear width, neck circumference, neck length, bodylength, tail length, tail diameter, height at sacrum and rump length were found as 54.13±3.48, 30.95±2.35, 18.65±2.06, 29.5±2.12, 18.66±1.22, 95.77±8.58, 53.32±4.56, 139.56±6.29, 103.51±12.55, 22.41±2.00, 135.77±4.40, 43.52±2.58 cm respectively. Results from univariate analysis of body measurement traits showed that most of the body measurements were low to moderate in heritablility. Overall range of heritability estimates for body measurements was found as 0.03±0.06 for neck circumference to 0.41±0.09 for tail length. Head length, tail length, tail diameter at base and ear length showed reasonably high estimates of heritability. The breeders preference for buffaloes with relatively smart head, thin tail and longer tail is supported through current study and these traits can be included for selection decisions for the production of replacement stock.
Keywords: body measurements; heritability; Nili Ravi buffalo; variance components